Investigation of Power Distribution on an Axial Fan - Hashim, Hafiz M.; Yasa, Yusuf; Dogruoz, M. Barris; Arik, Mehmet; Mese, Erkan (IEEE, 2016)
Forced convection cooling systems utilize fans which can be axial or radial, small or large in many different configurations. Efficiency of a fan depends on its electrical and mechanical designs as well as the environmental conditions that the fan is exposed to. Typically, the overall efficiency of an axial fan varies between 15 to 40 percent. Power losses may be due to electrical, aerodynamic or mechanical design components. Losses occurring in an axial fan motor have become a critical issue in which high inertial effects, low power, low cost and high efficiency are desired. In order to design an efficient motor, it is important to accurately predict the power losses which are normally dissipated in the form of heat. The present study starts with an investigation of the power losses of an axial fan experimentally and computationally. Moreover, it deals with modeling of mechanical, electrical, thermal and electromagnetic losses which focus especially on an outer rotor brushless DC motor. Reduction of these losses leads to a decrease in the motor temperature and, therefore, has a positive effect on the fan reliability. Expressions for calculating the inverter losses, motor losses and mechanical losses are derived. The power losses obtained are then used as heat sources when evaluating the thermal performance of the motor. By using a two-dimensional model, computational fluid dynamics (CFD) simulations are performed to determine the iron losses across the motor. These results are utilized to determine evaluate the overall efficiency of the system.
Keywords: Fan efficiency; BLDC motor; core loss; friction loss; inverter loss; torque; speed; Engineering